Kegiatan Senam Ergonomic Berbasis Spiritual untuk Mengurangi Nyeri Gout Arthritis pada Lansia di Wilayah SP.6 Sari Bunga Mas Lahat Tahun 2023: Ergonomic Exercise with Spiritual Basis Activity to Reduce Gout Arthritis Pain in Older Adults in SP.6 Sari Bunga Mas Lahat District Area in 2023 - Farama, Dodi Aflika; Gani, Abdul; Fauzia, Eri; Wibowo, Wahyu Dwi Ari (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Gout arthritis is an inflammatory joint disease often causing severe pain due to the accumulation of uric acid crystals in the joints. Typically, it results in swelling, redness, and pain in one or multiple joints, particularly in the big toe. This condition is associated with high levels of uric acid in the body, triggering harrowing gout attacks. Thus, physical activities and health education are initial steps in addressing pain complaints and elevations in uric acid levels among older adults and individuals with gout arthritis. This involves providing ergonomic exercise training through lectures, simulations, and practice sessions. The results show a reduction in pain intensity among older adults before and after the activity conducted over a month with four meetings. Furthermore, there is an expectation for the government and stakeholders to introduce scheduled and community-based structured activities as an initial step in addressing health issues, particularly among older adults.